TNF Patterns and Tumor Microenvironment Characterization in Head and Neck Squamous Cell Carcinoma - Long, Qian; Huang, Chunyu; Meng, Qi; Peng, Jin; Yao, Fan; Du, Dingfu; Wang, Xiaonan; Zhu, Wancui; Shi, Dingbo; Xu, Xiangdong; Qi, Xiang; Deng, Wuguo; et al. (Frontiers in Immunology, 2021)
Background: HNSCC is a heterogeneous disease, which arises from distinct anatomic subsites, associates with various risk factors and possesses diverse molecular pathological features. Generally, HNSCC is considered as an immunosuppressive disease, characterized by abnormal tumor immune microenvironment. The TNF family plays a crucial role in the survival, proliferation, differentiation, and effector functions in both immune and non-immune cells. However, the expression patterns of TNF in HNSCC remains to be systematically analyzed. Methods: We downloaded transcriptional profile data of HNSCC from TCGA and GEO datasets. Unsupervised clustering methods were used to identify different TNF patterns and classify patients for further analysis. PCA was conducted to construct a TNF relevant score, which we called risk score. Results: In this study, we systematically evaluated the patterns of TNF family and tumor immune microenvironment characteristics of HNSCC patients by clustering the expression of 46 members of TNF family. We identified two subtypes with distinct clinical and immune characteristics in HNSCC and constructed a risk scoring system based on the expression profile of TNF family genes. Conclusion: Risk score serves as a reliable predictor of overall survival, clinical characteristics, and immune cell infiltration, which has the potential to be applied as a valuable biomarker for HNSCC immunotherapy.